2016
DOI: 10.1159/000447409
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Central Foot Drop in a Pediatric Patient

Abstract: Foot drop is an inability to dorsiflex the ankle and toe. Primary causes of foot drop are compression or lesion of the 5th lumbar nerve and entrapment of the peroneal nerve at the head of the fibula. Rarely, some central nervous system lesions lead to foot drop. A 16-year-old boy was admitted with blunt head trauma that had happened in an assault. The muscle strength of the bilateral tibialis anterior, bilateral extensor digitorum longus and bilateral extensor digitorum brevis were Medical Research Council gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Most of the published FD cases due to central etiologies are due to brain lesions, including cerebral infarction, intra-cranial tumor, traumatic brain injury and multiple sclerosis [ 5 , 8 ]. Some articles reported that thoracic spine disc protrusion cases with FD could be due to UMNL [ [14] , [15] , [16] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the published FD cases due to central etiologies are due to brain lesions, including cerebral infarction, intra-cranial tumor, traumatic brain injury and multiple sclerosis [ 5 , 8 ]. Some articles reported that thoracic spine disc protrusion cases with FD could be due to UMNL [ [14] , [15] , [16] ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, in terms of central cervical etiology of FD, only one case of unilateral FD caused by a cervical spine lesion has been reported to date [ 3 ]. Central etiologies of FD are due to brain lesions [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reports of traumatic brain injury, and an anterior communicating artery intracranial aneurysm, presenting with acute bilateral foot drop highlight the need to exclude cranial/ central causes when no other pathology can be found [14,28,34]. Both the brain and spinal cord could be the source of the presentation due to specific vascular, neoplastic, infective, or demyelinating lesions.…”
Section: Discussionmentioning
confidence: 99%